2005
DOI: 10.1007/s11266-005-7726-y
|View full text |Cite
|
Sign up to set email alerts
|

What is Old is New Again: Achieving Effectiveness with Volunteer Programs in Kazakhstan

Abstract: This study based on Kazakhstan nonprofit organizations (NPOs) is the first to address the important issue of the relationship between volunteer management and volunteer program effectiveness in an international setting. Our inquiry is informed by findings of US scholars that show that the adoption of a recommended set of volunteer management practices is related to the level of effectiveness achieved with volunteer involvement in NPOs. The paper advances a path model to explain volunteer program effectiveness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Many volunteers need to know that they are appreciated, they make a difference, and the sensation of being recognized and esteemed is a significant factor that volunteers value (Cnaan and Cascio 1998). Some volunteers give importance to more formal recognition (Brudney 1990) such as dinners, gifts, certificates, plaques, trophies, or reference letters (Brudney and Nezhina 2005;Brudney 2005). The use of symbolic Voluntas rewards and recognition activities might be significant in explaining volunteer satisfaction (Farrell et al 1998), hours volunteered per month (commitment), length of service (tenure) (Cnaan and Cascio 1998), and retention (Hager and Brudney 2004).…”
Section: Management Factorsmentioning
confidence: 99%
“…Many volunteers need to know that they are appreciated, they make a difference, and the sensation of being recognized and esteemed is a significant factor that volunteers value (Cnaan and Cascio 1998). Some volunteers give importance to more formal recognition (Brudney 1990) such as dinners, gifts, certificates, plaques, trophies, or reference letters (Brudney and Nezhina 2005;Brudney 2005). The use of symbolic Voluntas rewards and recognition activities might be significant in explaining volunteer satisfaction (Farrell et al 1998), hours volunteered per month (commitment), length of service (tenure) (Cnaan and Cascio 1998), and retention (Hager and Brudney 2004).…”
Section: Management Factorsmentioning
confidence: 99%
“…Volunteers appreciate a "thank you" or "well done" when offered by beneficiaries or coordinators (Philips et al 2002;Hsieh et al 2007), and they also appreciate feeling they are part of a team, having a good work environment and someone showing personal interest in their life (Carvalho and Souza 2007). Some appreciate the more formal recognition given by organisations (Brudney 1990), such as being included in trips and events with other volunteers and staff (Hsieh et al 2007), dinners, gifts, certificates, plaques, trophies, reference letters or recognition in a newsletter (Brudney 1990;Brudney 2005;Brudney and Nezhina 2005;Carvalho and Souza 2007;Woods 2006). The use of symbolic rewards and recognition activities is significant in explaining volunteer satisfaction (Farrell et al 1998), hours volunteered per month (commitment), length of service (tenure) (Cnaan and Cascio 1998) and retention (Hager and Brudney 2004).…”
Section: Volunteer Satisfactionmentioning
confidence: 99%
“…For instance, a large literature exists around formalizing the entire practice of volunteerism including forming voluntary boards and committees, developing job descriptions and evaluation measures, and requiring training and orientation sessions (Barman 2007;Brudney and Nezhina 2005;Helmig et al 2004;Howe 1991;Leiter 2008;Kim et al 2007). Many organizations adhere to this approach because it is believed that thorough selection, screening, training, and orientation are linked with a job well done by volunteers (Crompton 1999).…”
Section: Volunteering and Volunteer Engagementmentioning
confidence: 99%
“…The similarity among organizations or isomorphism in the voluntary sector is becoming evident, revealing that nonprofit organizations share many structural characteristics (i.e., departmentalization, hierarchical levels, formalizations, autonomy, work intensity, organizational age) (Leiter 2008). A study by Brudney and Nezhina (2005) strengthens this argument because they essentially studied whether a formalized volunteer program was related to program effectiveness outside of the West, and concluded that written policies to govern the volunteer program, job descriptions for volunteers, basic/on-going training, and resources to manage volunteers, held up in Kazakhstan.…”
Section: Volunteering and Volunteer Engagementmentioning
confidence: 99%
See 1 more Smart Citation